2012
DOI: 10.9734/ejmp/2012/1488
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Microwave-Assisted Hydrodistillation with the Traditional Hydrodistillation Method in the Extraction of Essential Oils from Ferulago angulata (Schelcht.) Boiss

Abstract: This work was carried out in collaboration between all authors. JS designed the study, wrote the protocol, and wrote the first draft of the manuscript. CKT managed the literature searches, analyses of the study performed the spectroscopy analysis and MM managed the experimental process and MA identified the species of plant. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…[9,10,30] Chemical compounds and biological activity of some species from the genus Ferulago have been the subject of preceding studies. [8,9,14,17] The reports on the chemical compositions of the oils isolated from the aerial parts F. angulata are abundant [6,7,11,13,[30][31][32] as most of these investigations showed patterns of oil compositions similar to our present study. Although differences can be observed in the percentage distribution, in conformity with our findings (Z)-β-ocimene and α-pinene were dominant oil compounds in an earlier investigation.…”
Section: Oil Analysissupporting
confidence: 79%
“…[9,10,30] Chemical compounds and biological activity of some species from the genus Ferulago have been the subject of preceding studies. [8,9,14,17] The reports on the chemical compositions of the oils isolated from the aerial parts F. angulata are abundant [6,7,11,13,[30][31][32] as most of these investigations showed patterns of oil compositions similar to our present study. Although differences can be observed in the percentage distribution, in conformity with our findings (Z)-β-ocimene and α-pinene were dominant oil compounds in an earlier investigation.…”
Section: Oil Analysissupporting
confidence: 79%
“…Some extraction using the microwave that has been successfully developed is microwave hydrodistillation method which is a combination of hydrodistillation with microwave heating 4 . This is supported by previous studies that had been conducted by Asghari et al 5 which showed that the extraction of essential oil from Ferulago angulata using microwave hydrodistillation method is more effective and efficient when compared with hydrodistillation method. Based on these research, the extraction of essential oil from Ferulago angulata using microwave hydrodistillation method with feed to solvent ratio of 0.067 g/mL and microwave power of 650 W for 70 minutes obtained a yield of 3.8%.…”
Section: Introductionsupporting
confidence: 82%
“…Based on these research, the extraction of essential oil from Ferulago angulata using microwave hydrodistillation method with feed to solvent ratio of 0.067 g/mL and microwave power of 650 W for 70 minutes obtained a yield of 3.8%. While for the extraction of essential oil from Ferulago angulata using hydrodistillation method with feed to solvent ratio of 0.083 g/mL for 3 hours obtained a yield of 1.7% 5 . Therefore, in this study conducted extraction of patchouli oil using microwave hydrodistillation method.…”
Section: Introductionmentioning
confidence: 99%
“…The refractive indices, specific gravities and color of EO obtained from thyme aerial parts for both MAHD and HD fall within the ranges quantified by Food Chemical Codex (FCC). GC-MS analysis of the extracted EO shown that the use of microwave energy did not adversely affect the composition of the EO 46 .…”
Section: Applications Microwave Assisted Oil Extractionmentioning
confidence: 99%